Role of tectonic stress in seepage evolution along the gas hydrate‐charged Vestnesa Ridge, Fram Strait - Plaza-Faverola, Andreia; Bünz, Stefan; Johnson, Joel E; Chand, Shyam; Knies, Jochen; Mienert, Jurgen; Franek, Peter (Geophysical Research Letters, 2015)
Source at https://doi.org/10.1002/2014GL062474 . An edited version of this paper was published by AGU. Copyright 2015 American Geophysical Union. Methane expulsion from the world ocean floor is a broadly observed phenomenon known to be episodic. Yet the processes that modulate seepage remain elusive. In the Arctic offshore west Svalbard, for instance, seepage at 200–400 m water depth may be explained by ocean temperature‐controlled gas hydrate instabilities at the shelf break, but additional processes are required to explain seepage in permanently cold waters at depths >1000 m. We discuss the influence of tectonic stress on seepage evolution along the ~100 km long hydrate‐bearing Vestnesa Ridge in Fram Strait. High‐resolution P‐Cable 3‐D seismic data revealed fine‐scale (>10 m width) near‐vertical faults and fractures controlling seepage distribution. Gas chimneys record multiple seepage events coinciding with glacial intensification and active faulting. The faults document the influence of nearby tectonic stress fields in seepage evolution along this deepwater gas hydrate system for at least the last ~2.7 Ma.